FINANCIAL DISTRESS PADA PERUSAHAAN PROPERTY DAN REALESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2016-2019 - Budi, Cindy Sinthia; Dillak, Vaya Juliana (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.03.TAHUN.2022, 2022)
Financial Distress can be used as an early warning before bankruptcy so that the company's management can take quick decisions to prevent problems before the company reaches the bankruptcy phase. This study aims to determine the effect of Capital Structure, Liquidity, Inflation and Company Size on Financial Distress in Property and Real Estate Sub-Sector Companies Listed on the Indonesia Stock Exchange for the 2016-2019 Period. In this study, purposive sampling was used and obtained 33 companies with a research period of 4 years, so 132 samples were obtained. The data analysis technique in this study is quantitative analysis using descriptive statistics and logistic regression analysis methods using the SPSS IBM 25 application. The results of the study show that the variables of Capital Structure, Liquidity, Inflation and Firm Size simultaneously have an effect on Financial Distress. Partially, the Capital Structure and Liquidity variables have an effect on Financial Distress, while the Inflation and Firm Size variables have no effect on Financial Distress. Based on the results of this study, it is hoped that future researchers will develop other independent variables. Investors are advised to invest in companies that have a DER level below the safe limit of 50% and companies that have total assets much higher than their total debt.